A clutter suppression algorithm via subspace‐weighted mixed‐norm minimisation - Wang, Degen; Wang, Tong; Cui, Weichen; Zhang, Xinying (IET radar, sonar & navigation, 2023)
Space‐time adaptive processing (STAP) struggles to effectively suppress clutter in the heterogeneous clutter environment due to the lack of training samples. In order to enhance clutter suppression performance of STAP, a subspace‐weighted mixed‐norm minimisation approach is given. First, a roughly estimated clutter subspace is obtained using the subspace augment (SA) approach. The weight vector is then designed using the association between the dictionary matrix and the noise subspace, allowing the algorithm to penalise sparse coefficients democratically. Finally, in order to solve the subspace‐weighted mixed‐norm minimisation problem, we derive a fast algorithm based on the alternating direction multiplier method (ADMM) framework. The proposed algorithm does not require iteratively updating the weight vector in contrast to the iterative re‐weighted l1 ${l}_{1}$ (IRL1) algorithm. The simulation results demonstrate the effectiveness of the proposed algorithm in terms of computational efficiency and clutter suppression performance. In the paper, a subspace‐weighted mixed‐norm minimisation approach is proposed, and the alternating direction multiplier method (ADMM) algorithm is utilised to solve the subspace‐weighted mixed‐norm minimisation problem.